2020
DOI: 10.3390/agronomy10040530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjuvants and pH Adjuster on the Efficacy of Sulcotrione Herbicide

Abstract: The effectiveness of herbicides is affected by the pH of the spray liquid. The use of adjuvants can mitigate the negative effect of pH, and it also allows for a reduction in herbicide doses while maintaining high efficiency. Greenhouse studies were performed to evaluate the efficacy of the herbicide sulcotrione (HRAC F2), against barnyardgrass, at full or reduced doses with adjuvants, and a modified pH of the solutions. The contact angle and surface tension of liquid spray drops, as well as the shear viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Most tank-mix adjuvants aim for reducing evaporation, spray drift, and volatilization and improving pesticide’s ability to spread and stick on the target surface by reducing CA ( Celen, 2010 ; Melo et al, 2015 ; Santos, Ferreira & Viana, 2019 ). The addition of tank-mix adjuvant(s) into a pesticide product or pesticide spray mixture contributes to the reduction of spraying droplets’ CAs, which is expected to reduce off-target deposit effectively and obtain a better distribution ( Griesang et al, 2017 ; Mehdizadeh, Mehdizadeh & Baghaeifar, 2020 ; Meng et al, 2018 ; Sobiech et al, 2020 ). Therefore, some tank-mix adjuvants are able to reduce the amount of pesticide usage, enhance control efficacy, facilitate the delivery of pesticide chemicals, and alleviate environmental pollution ( Jibrin et al, 2021 ; Li et al, 2021 ; Meng et al, 2018 ; Preftakes et al, 2019 ; Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most tank-mix adjuvants aim for reducing evaporation, spray drift, and volatilization and improving pesticide’s ability to spread and stick on the target surface by reducing CA ( Celen, 2010 ; Melo et al, 2015 ; Santos, Ferreira & Viana, 2019 ). The addition of tank-mix adjuvant(s) into a pesticide product or pesticide spray mixture contributes to the reduction of spraying droplets’ CAs, which is expected to reduce off-target deposit effectively and obtain a better distribution ( Griesang et al, 2017 ; Mehdizadeh, Mehdizadeh & Baghaeifar, 2020 ; Meng et al, 2018 ; Sobiech et al, 2020 ). Therefore, some tank-mix adjuvants are able to reduce the amount of pesticide usage, enhance control efficacy, facilitate the delivery of pesticide chemicals, and alleviate environmental pollution ( Jibrin et al, 2021 ; Li et al, 2021 ; Meng et al, 2018 ; Preftakes et al, 2019 ; Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sobiech et al. (2020) demonstrated that the addition of NIS to sulcotrione solutions reduced dST by 20.8 mN m −1 compared to sulcotrione alone. Surfactants typically reduce the surface tension of a solution between 30 and 50 mN m −1 (Curran et al., 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Sobiech et al. (2020) reported that at 60% RH CA of sulcotrione solutions containing NIS was 20.2° smaller than sulcotrione alone. Although sCA is directly related to dST, some of the adjuvant solutions that presented lower dST in relation to formulations alone did not necessarily present lower sCA.…”
Section: Resultsmentioning
confidence: 99%
“…However, the authors observed that a reduction in pH improved control when using half a dose, suggesting that the spray solution acidification may assist the herbicide treatment under more extreme situations. Sobiech et al (2020) also stated that the use of pH reducers and small water hardness can be of great importance when using reduced herbicide doses.…”
Section: Areamentioning
confidence: 99%